2020
DOI: 10.1017/s0031182020001286
|View full text |Cite
|
Sign up to set email alerts
|

Angiostrongylus cantonensis (rat lungworm) in Florida, USA: current status

Abstract: Angiostrongylus cantonensis has been found in Florida, USA, from the panhandle in the north to Miami and surrounding areas in the southern parts of the state, in both definitive and intermediate hosts in a limited studies completed in 2015. Additional studies have identified this parasite in a variety of intermediate hosts, both native and non-native gastropod species, with new host species recorded. Many areas in Florida with higher A. cantonensis prevalence were those with a high human population density, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…Ongoing spread of the major DHs and IHs of A. cantonensis has led to an almost-global distribution of AEM within the tropics [2]. The majority of clinical cases of AEM are reported from South-East Asia; however, the disease is also prominent in Pacific regions (French Polynesia, Hawai'i, and Australia) with recent invasions into the continental United States [3,74]. Closer to Europe, A. cantonensis had already been detected in Egypt by the late 1970s, representing the first reports on its occurrence in the broader Mediterranean basin [75].…”
Section: Spread To Europementioning
confidence: 99%
“…Ongoing spread of the major DHs and IHs of A. cantonensis has led to an almost-global distribution of AEM within the tropics [2]. The majority of clinical cases of AEM are reported from South-East Asia; however, the disease is also prominent in Pacific regions (French Polynesia, Hawai'i, and Australia) with recent invasions into the continental United States [3,74]. Closer to Europe, A. cantonensis had already been detected in Egypt by the late 1970s, representing the first reports on its occurrence in the broader Mediterranean basin [75].…”
Section: Spread To Europementioning
confidence: 99%
“…Not only are clinical cases of neuroangiostrongyliasis steadily increasing [ 86 ], but recent studies have recorded A. cantonensis in areas where it was previously unknown [ 3 , 41 , 42 , 45 , 46 , 152 ]. This spread is facilitated by increasing globalisation leading to the further introduction of infected rats and other invasive host species, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, A. cantonensis has been recorded in other areas, including additional Caribbean islands [ 20 , 39 , 40 ], Mallorca [ 41 ] and the Canary Islands [ 42 ]. It is now widely distributed across many tropical/subtropical regions globally [ 3 , 13 , 43 ], as well as a few more temperate localities [ [44] , [45] , [46] ].…”
Section: Introductionmentioning
confidence: 99%
“…Given reports from Volusia, Miami-Dade, Orange, Hillsborough, Alachua, St. Johns, and Leon Counties of the zoonotic nematode parasite Angiostrongylus cantonensis's, the rat lungworm, and nine other parasites found in CTF individuals, euthanized frogs could be sent to scientists to better understand parasite loads (Ortega et al 2015, Walden et al 2020, Chase et al 2022. Ortega et al (2022) observed that CTF biomass was not negatively impacted by infections with at least one parasitic nematode, Aplectana hamatospicula, and CTF shed more nematode worms in their feces than native frogs.…”
Section: Declarationsmentioning
confidence: 99%